Does the longus colli have an effect on cervical vertigo?: A retrospective study of 116 patients. Issue 12 (March 2017) - Liu, Xiao-Ming; Pan, Fu-Min; Yong, Zhi-Yao; Ba, Zhao-yu; Wang, Shan-Jin; Liu, Zheng; Zhao, Wei-dong; Wu, De-Sheng
Abstract : Abstract: The aim of the study was to evaluate the role of the longus colli muscles in cervical vertigo. We retrospectively analyzed 116 adult patients who underwent anterior cervical discectomy and fusion (ACDF) during 2014 in our department. Patients were assigned to the vertigo group or the nonvertigo group. Demographic data were recorded. Inner distance and cross-sectional area (CSA) of longus colli were measured using coronal magnetic resonance imaging (MRI). The vertigo group (n = 44) and the nonvertigo group (n = 72) were similar in demographic data. Mean preoperative Japanese Orthopaedic Association (JOA) score was higher in the vertigo group than in the nonvertigo group ( P  = 0.037), but no difference postoperatively. Mean JOA scores increased significantly postoperatively in both groups ( P  = 0.002 and P  = 0.001). The mean vertigo score decreased significantly from pre- to postoperatively in the vertigo group ( P  = 0.023). The mean preoperative Cobb angle was significantly smaller in the vertigo group than in the nonvertigo group ( P <0.001), but no significant difference postoperatively. After ACDF, the mean Cobb angle increased significantly in the vertigo group ( P <0.001). The instability rates of C3/4 and C4/5 were significantly higher in the vertigo group ( P <0.001 and P <0.001). The inner distance of longus colli was significantly shorter ( P  = 0.032 and P  = 0.026) and CSA significantly smaller ( P  = 0.041 and P  = 0.035), at C3/4 and C4/5 in the vertigo group than in the nonvertigo group. Mean Miyazaki scores were significantly higher in the vertigo group at C3/4 and C4/5 ( P  = 0.044 and P  = 0.037). Moreover, a shorter inner distance and smaller CSA were related to a higher Miyazaki score. Inner distance and cross-sectional area (CSA) of longus colli are associated closely with cervical vertigo. Shorter inner distance and smaller CSA of the longus colli muscles might be risk factors for cervical vertigo. ACDF provided a good resolution of cervical vertigo.